Granular cell astrocytoma: an aggressive IDH‐wildtype diffuse glioma with molecular genetic features of primary glioblastoma. (10th October 2018) - Vizcaino, M. Adelita; Palsgrove, Doreen N.; Yuan, Ming; Giannini, Caterina; Cabrera‐Aldana, Eibar Ernesto; Pallavajjala, Aparna; Burger, Peter C.; Rodriguez, Fausto J.
Abstract: Granular cell astrocytoma (GCA) is a rare adult infiltrating glioma subtype. We studied a series of 39 GCAs. Median age of presentation was 57.8 years and most cases developed in the frontal or temporal lobes. Tumors included grade II (n = 14), grade III (n = 11), and grade IV (n = 14) by WHO criteria. Granular cell morphology was diffuse in 31 (79%) cases and partial in eight (21%). Immunohistochemistry showed frequent positivity for GFAP (28 of 31), OLIG2 (16 of 16), and CD68 (27 of 30), but HAM56, CD163, and IBA‐1 histiocytic markers were all negative (22 of 22). IDH1(R132H) was negative in all the cases tested (16 of 16), while ATRX expression was retained (12 of 12). Cytogenetics demonstrated monosomy 10 (6 of 6) cases, +7 in 4 (of 6), −13q in 4 of 6, and −14 in 4 of 6. Next‐generation sequencing demonstrated mutations in PTEN/PIK3 genes in 6/13 (46%), NF1 in 3 of 10 (30%), TP53 in 3 of 13 (23%), PALB2 in 3 of 10 (30%), STAG2 in 3 of 10 (30%), EGFR mutation/amplification in 3 of 13 (23%), and AR in 2 of 10 (20%). CDKN2A/B deletion was identified in 5 of 13 (30%) cases (homozygous deletion in 4). The TERT C228T mutation was identified in 9 of 13 (69%). No mutations were encountered in IDH1, IDH2, CIC, FUBP1, H3F3A, BRAF or ATRX genes. The mean overall survival was 11.3 months. Patients >60 years old at diagnosis had a worse survival than patients <60 years ( P  = 0.001). There were no statistically significant differences in survival by WHO grade, extent of granular cell change, sex or MIB‐1 ( P  > 0.05). GCA is a variant of IDH‐wildtype diffuse glioma with aggressive behavior irrespective of grade and extent of granular cell morphology, and with molecular genetic features corresponding to primary glioblastoma.